Estimating the Value of Travel Time to Recreational Sites Using Revealed Preferences - Carlo Fezzi; Ian J. Bateman; Silvia Ferrini (Fondazione Eni Enrico Mattei (FEEM), 2013)
The opportunity Value of Travel Time (VTT) is one of the most important parts of the total cost of day-long recreational activities and arguably the most difficult to estimate. While numerous studies have criticized the use of salaries to proxy the relevant shadow values, a consensus on an alternative measure still has to emerge. This paper uses a revealed preference approach to estimate the VTT for recreational trips by modeling individuals' preferences for toll roads and deriving their willingness-to-pay to reduce travel time. Our case-study sites are three beaches located in the Italian Riviera Romagnola, whose road network is a mix of toll and free access roads. By carrying-out face-to-face interviews, we reconstruct respondents' routes, indentify their time-cost trade-offs and ultimately estimate their VTT. Results show considerable heterogeneity in values with the VTT for day-long recreational visits being significantly higher than the one of longer holidays.
Keywords: Q50; 330; Value of Time; Value of Travel Time Savings; Recreation Demand Models; Revealed Preferences; Willingness to Pay Space